Cellular variations of the oral mucous in patients with complete dental prosthesis - Alina Rodríguez Castellanos; Zulema Arias Arañó; Ayvanka León Quintela; Humberto Manuel Rodríguez Rey (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The complete dental prosthesis generates a tisular reaction in the oral cavity which diagnosis can be confirmed by means of citological study that constitutes an indispensable tool to identify early dysplastic changes of the subprosthesis mucous.  Objective: To identify the oral possible cellular variations of the oral mucous in patients with complete prosthesis.  Methods: A descriptive and cross sectional study was carried out in  Mártires del Moncada Provincial Stomatological Clinic of Santiago de Cuba, from June, 2014 to January, 2019, with 100 patients, assisted in the Stomatological Prosthesis Department to whom the cytological  scrapings of the palate and the edges were carried out for their later microscopic analysis according to variables of interest. For the statistical procedures, the percentage was used as summary measure and the Chi squared statistician, with a significance level of 0,05.  Results: In the series the mild dysplasias prevailed (66,7%) that were more frequent in the  20 to 39 age group (12,5%), while  the moderate and the serious dysplasias figured mainly in the age group of 60 and over (9,3 and 27,7%, respectively). All the dysplasia types prevailed in the patients that had carried the prosthesis for more than 5 years and they mostly affected the keratin; in a same way, among the observed lesions, the stomatitis affected a higher percentage (31,2), mainly in the palate (82,3%), while 8,3% corresponded to the leukoplakia.  Conclusion: The cytological checkups are indispensable for the diagnostic confirmation of dysplasic changes and they allow to prevent early oral cancer.